1999
DOI: 10.1109/3.748831
|View full text |Cite
|
Sign up to set email alerts
|

Optical studies of laser-induced gray-tracking in KTP

Abstract: We have studied gray-tracking induced by a pulsed and polarized 532-nm laser beam in flux grown KTiOPO 4 (KTP) crystals. Transmission spectra measured under polarized light give different results: gray-tracking leads to an increase in the initial anisotropy of the linear optical properties of KTP, and the polar axis is the most sensitive to this process. The dynamics of relaxation of gray-tracking is anisotropic and depends on the wavelength under analysis. We show a possible induced modification of the crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(48 citation statements)
references
References 17 publications
4
43
0
1
Order By: Relevance
“…The gray-tracking changes the optical properties of the KTP crystal when the crystal is illuminated by visible light beam. The mechanism of gray tracking is not quite clear but a possible explanation is based on the trapping of the holes and electrons by Fe (impurity) and Ti ions, respectively [10]. On the other hand the manifestation of gray-tracking is well known, usually very transparent in the IR region KTP (and also PPKTP) starts to exhibit an increased level of absorption after being exposed to the pump beam.…”
Section: Modeling Of the Cavity Geometry Bandwidthmentioning
confidence: 99%
“…The gray-tracking changes the optical properties of the KTP crystal when the crystal is illuminated by visible light beam. The mechanism of gray tracking is not quite clear but a possible explanation is based on the trapping of the holes and electrons by Fe (impurity) and Ti ions, respectively [10]. On the other hand the manifestation of gray-tracking is well known, usually very transparent in the IR region KTP (and also PPKTP) starts to exhibit an increased level of absorption after being exposed to the pump beam.…”
Section: Modeling Of the Cavity Geometry Bandwidthmentioning
confidence: 99%
“…Crystal losses in the infrared comes mainly from surface reflection, reduced by anti-reflective coating (R = 0.1 %), since crystal absorption at this wavelength is small (0.05 %). For the pump, we have reflection losses (R = 0.5 %) and crystal absorption, increased by gray-tracking effects [21]. The cavity length is controlled by a piezo actuator on the mirror, and the cavity is kept nearly confocal, in order to help the alignment and reduce the consequences of the walk-off.…”
Section: Methodsmentioning
confidence: 99%
“…These marks need long time to disappear on their own and the crystal in this case rather demands an active healing treatment known as thermal annealing [47]. The investigations by [8,10,9,19,69] have shown that the transparency of the crystal changes after the exposure to the blue pump beam. Above mentioned papers measure the absorption after the exposure.…”
Section: Optimal Focusing In the Crystal And Thermal Lensingmentioning
confidence: 99%
“…The measurements show that the absorption increases but not on the level as described in [8,10,9,19,69]. Our measurements were performed on the crystal which was not illuminated by blue light for more than 4 days before.…”
Section: Optimal Focusing In the Crystal And Thermal Lensingmentioning
confidence: 99%